Impact of Legal Representation on Child Custody Decisions among Families with a History of Intimate Partner Violence in King County, Washington, 2000-2010 - Kernic, Mary A. ([Verlag nicht ermittelbar], 2017)
These data are part of NACJD's Fast Track Release and are distributed as they there received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except of the removal of direct identifiers. Users should refer to the accompany readme file for a brief description of the files available with this collections and consult the investigator(s) if further information is needed. The major aim of this study was to test the hypothesis that legal representation of the Intimate Partner Violence (IPV) victim in child custody decisions leads to greater legal protections being awarded in these decisions compared to similar cases of unrepresented IPV victims. A retrospective cohort study was conducted among King County couples with minor children filing for marriage dissolution in King County, Washington between January 1, 2000 and December 31, 2010 who had a history of police or court documented intimate partner violence (IPV). The study examined the separate effects of private legal representation and legal aid representation relative to propensity score-matched, unrepresented comparison subjects. Primary study outcomes were measured at the time the first "Final Parenting Plan" was awarded. Researchers also examined the two-year period post-decree among the subset of cases with filing between January 1, 2000 and December 31, 2009 for post-decree court proceedings indicative of continued child custody or visitation disputes.